A graveyard for lunatics : another tale of two cities - Bradbury, Ray, 1920- (New York : Distributed by Random House, 1990)
A sci-fi film writer discovers a body frozen in time and poised to climb from the city of the dead to the city of light.
School Library Journal.
Wilson's Fiction.
Wilson's Senior High School.
Young Adult
Keywords: Science fiction; Science fiction